2019
DOI: 10.1136/heartjnl-2019-315174
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial dimension and cardiovascular outcomes in patients with and without atrial fibrillation: a systematic review and meta-analysis

Abstract: ObjectiveThe prognostic value of left atrial (LA) dimensions may differ between patients with and without atrial fibrillation (AF).MethodsMEDLINE and EMBASE were searched for studies that investigated the association between LA echocardiographic parameters measured by transthoracic echocardiography and cardiovascular outcomes in patients with or without AF. Data were independently abstracted by two reviewers and pooled using random-effects meta-analysis. The primary outcome was incident stroke or thromboemboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 29 publications
0
26
0
2
Order By: Relevance
“…[22][23][24] In healthy subjects, LAVI is not influenced by age, 25 is closely related to diastolic dysfunction, and is a powerful predictor of AF as well as other cardiovascular events. 26 In the absence of LVZs, patients with persistent AF undergoing PVI alone have clinical outcomes comparable to those with paroxysmal AF, 27 and, in a recent study, the efficacy of cryoballoon ablation in paroxysmal and persistent AF was equivalent when LAVI was less than 61 mL/m 2 . 28 Interestingly, LVZs detected by EAVM and the fibrotic content detected by LGE-MRI were associated with larger LA volume and were predictive of AF recurrence in paroxysmal as well as persistent AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] In healthy subjects, LAVI is not influenced by age, 25 is closely related to diastolic dysfunction, and is a powerful predictor of AF as well as other cardiovascular events. 26 In the absence of LVZs, patients with persistent AF undergoing PVI alone have clinical outcomes comparable to those with paroxysmal AF, 27 and, in a recent study, the efficacy of cryoballoon ablation in paroxysmal and persistent AF was equivalent when LAVI was less than 61 mL/m 2 . 28 Interestingly, LVZs detected by EAVM and the fibrotic content detected by LGE-MRI were associated with larger LA volume and were predictive of AF recurrence in paroxysmal as well as persistent AF.…”
Section: Discussionmentioning
confidence: 99%
“…LAVI provided a more accurate assessment of LA remodeling, and is known to be independently associated with AF recurrence after cardioversion or catheter ablation 22–24 . In healthy subjects, LAVI is not influenced by age, 25 is closely related to diastolic dysfunction, and is a powerful predictor of AF as well as other cardiovascular events 26 …”
Section: Discussionmentioning
confidence: 99%
“…The study by Froehlich et al ,2 published in Heart , provides a new insight into this important subject. This study presents a systematic review and a meta-analysis of 91 observational studies exploring the association between several indices of LA dilatation and outcomes in patients with AF (23 studies with a total of 14 936 participants) and those without AF (68 studies with a total of 50 720 patients).…”
mentioning
confidence: 99%
“…Thus, LA dilatation appears to be a biomarker of left ventricular dysfunction, rather than a determinant of the future development of HF. This concept is challenged by the study by Froehlich et al ,2 suggesting an independent prognostic significance of LA dilatation for incident HF in patients with or without AF and a wide variety of associated cardiovascular disorders. In support of this observation, a recent study demonstrated that LAVI was an independent predictor of adverse cardiovascular outcomes, including HF, following first myocardial infarction 7.…”
mentioning
confidence: 99%
“…However, it remains unclear whether this association is simply related to AF or whether LA size also is an important prognostic variable. In a meta-analysis of over 50 000 patients from studies that included patients with (n=23) or without (n=68) AF, Froehlich and colleagues1 found stronger associations between LA size and cardiovascular outcomes in patients without compared with those with AF (figure 1). For example, a larger LA diameter was significantly associated with stroke and thromboembolic events (risk ratio (RR) 1.38, 95% CI 1.02 to 1.87; p=0.03) in patients without AF, but not in those with AF (RR 1.02, 95% CI 0.98 to 1.07; p=0.27; p for difference=0.05).…”
mentioning
confidence: 99%